2020
DOI: 10.1016/j.chest.2020.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Cardiovascular Events in Patients With COPD and Preceding Hospitalization for Acute Exacerbation

Abstract: The accuracy of the diagnoses in this database regarding COPD, AMI, ischemic stroke, and ICH has been previously validated. 19-22 The three study cohorts were defined as patients with COPD experiencing first-time AMI (n ¼ 26,442), ischemic stroke (n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 42 publications
1
23
0
2
Order By: Relevance
“…Many studies have reported an increased risk of cardiovascular events in patients with acute exacerbation of COPD, especially within the first 30 days after acute exacerbation (22)(23)(24). Therefore, in addition to paying greater attention to the treatment of patients with COPD and COVID-19 during hospitalization, it is also important to follow up these patients for some time after rehabilitation, to further reduce mortality (25).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported an increased risk of cardiovascular events in patients with acute exacerbation of COPD, especially within the first 30 days after acute exacerbation (22)(23)(24). Therefore, in addition to paying greater attention to the treatment of patients with COPD and COVID-19 during hospitalization, it is also important to follow up these patients for some time after rehabilitation, to further reduce mortality (25).…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalised AECOPD are associated with substantial mortality and an enriched risk of subsequent major adverse cardiovascular events [2,3]. Hospitalisation therefore represents a favourable opportunity to diagnose and intervene in cardiac disease by implementing wellestablished treatment pathways with recognised treatment benefits [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Acute Exacerbations of Chronic Obstructive Pulmonary Disease (AECOPD) are complex, heterogenous events accompanied by a surge in cardiovascular risk and death [1][2][3]. Cardiac involvement, manifest as biomarkers of myocardial dysfunction, can be detected in up to 60% of acute exacerbations [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In a recent study, patients with COPD are at a higher risk of cardiovascular mortality. 4 COPD is characterized by dyspnea, poor health-related quality of life (HRQL), and insufficient cardiorespiratory endurance during exercise. 5 Even in patients with mild COPD, exercise performance is compromised, and exercise intolerance is also common.…”
Section: Introductionmentioning
confidence: 99%